2017
DOI: 10.1016/j.bbmt.2017.03.035
|View full text |Cite
|
Sign up to set email alerts
|

A Time-to-Event Model for Acute Kidney Injury after Reduced-Intensity Conditioning Stem Cell Transplantation Using a Tacrolimus- and Sirolimus-based Graft-versus-Host Disease Prophylaxis

Abstract: There is a paucity of data evaluating acute kidney injury (AKI) incidence and its relationship with the tacrolimus-sirolimus (Tac-Sir) concentrations in the setting of reduced-intensity conditioning (RIC) after allogeneic stem cell transplantation (allo-HSCT). This multicenter retrospective study evaluated risk factors of AKI defined by 2 classification systems, Kidney Disease Improving Global Outcome (KDIGO) score and "Grade 0-3 staging," in 186 consecutive RIC allo-HSCT recipients with Tac-Sir as graft-versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…Tacrolimus-induced nephrotoxicity, which manifests as AKI, is a common treatment-emergent toxicity [56]. Achieving the tacrolimus target trough is important to reduce nephrotoxicity resulting from supratherapeutic tacrolimus concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Tacrolimus-induced nephrotoxicity, which manifests as AKI, is a common treatment-emergent toxicity [56]. Achieving the tacrolimus target trough is important to reduce nephrotoxicity resulting from supratherapeutic tacrolimus concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…CMV, cytomegalovirus; PCR, polymerase chain reaction [Color figure can be viewed at wileyonlinelibrary.com] in our prior experience. 23 However, 1 retrospective study showed that concentrations >10 ng/mL up to day +14 after stem cell infusion (not afterwards) resulted in a higher risk of transplant-associated microangiopathy when combined with tacrolimus. 45 Although an increase in sirolimus levels appears to be an attractive option to control CMV-DNAemia, nevertheless, such an increase could lead to relevant dose-dependent side effects such as hypercholesterolemia and hypertriglyceridemia, cardiovascular risk, mTOR-I-associated edema, and proteinuria with impaired glomerular filtration rate that should be monitored and controlled by lowering sirolimus doses when deemed appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…CMV, cytomegalovirus; PCR, polymerase chain reaction [Color figure can be viewed at wileyonlinelibrary.com]in our prior experience 23. Points represent median values.…”
mentioning
confidence: 99%
“…An integrated version of these 2 was issued in 2012 in the form of the new Kidney Disease: Improving Global Outcomes (KDIGO) guideline, which has since become widely used for the diagnosis of AKI [9]. Although there have been a number of reports using the Risk, Injury, Failure, Loss of kidney function, and Endstage kidney function or AKI network criteria to evaluate and study posttransplant AKI [10], only a limited number of reports have used the KDIGO criteria to study renal dysfunction associated with allo-HSCT [11]. The lack of a uniform definition of AKI has hindered the interpretation of previous studies.…”
Section: Introductionmentioning
confidence: 99%